Religious Pluralism and Socio-Cultural Integration - Noggler, Othmar (Journal of Dharma, 1983)
Coming from a European or Latin American background I should like to stress primarily religious pluralism rather than a pluralism of religions — by which is meant a variety of religions - though both exist in my country as well as in Latin America. Religious pluralism permits me to speak in the light of my own background and, I wish to apologize for my being rather hard in my observations, for example, neglecting important religions of small minorities converted from an occidental background to an oriental religion. As already mentioned, it is an altogether different worldview and, consequently, an entirely different approach to social, economic, socio-cultural and political situations, which makes basic worldview so meaningful for any sociocultural integration of a given culture or nation.